Structure and specific carbon in a chronosequence of Teobroma cocoa L. agroforestry systems in Tabasco, México - Salvador-Morales, Pedro; Martínez-Sánchez, Jose Luis; Cámara Cabrales, Luisa; Zequeira Ramos, Carolina (Instituto de Ecología, A.C., 2020)
Given the determining factor that constitutes land use change (LUC) upon biodiversity loss and environmental deterioration, cocoa-shade agroforestry systems can represent an important land area for biodiversity conservation and carbon storage. The aim of this study was to investigate the effect of the age of the cocoa agroforestry systems on their shade tree diversity and carbon stocks. Two-hundred and fifty-eight plots were compared in eleven cocoa plots between 10 and 70 yr-old, totalizing 7.87 ha. The normal tree girth (DN) and total height of all trees > 5 cm DN were measured, and their estimated biomass were compared using a general and a species-specific allometric equation to know the discrepancy between both methods.  The 70 yr-old plantations presented more species per hectare (23), Shannon diversity index (2.0) and carbon storage (75 Mg ha-1) than the 10 yr-old plantations (p < 0.01; mean values of 10 Mg ha-1, 1.1 Mg ha-1 and 36 Mg ha-1; respectively). Specific allometric equations estimated 27.7% (p = 0.05) more aboveground biomass than the general equation, so they are considered as more precise to this specific agroforestry system and hence are recomended. It is concluded that, particularly for México, conservation of mature cocoa-agroforestry systems contribute to the conservation of tree biodiversity and carbon stocks of tropical vegetation, resembling relics of the original vegetation.